2016
DOI: 10.1021/acs.jpcb.6b06683
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydration Layer in Dynamical Transition in Proteins: Insights from Translational Self-Diffusivity

Abstract: Elucidation of the role of hydration water underpinning dynamical crossover in proteins has proven challenging. Indeed, many contradictory findings in the literature seek to establish either causal or correlative links between water and protein behavior. Here, via molecular dynamics, we compute the temperature dependence of mean-square displacement and translational self-diffusivities for both hen egg white lysozyme and its hydration layer from 190 to 300 K. We find that the protein's mobility increases sharpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Many other theoretical studies have been systematically investigated on this surface, such as the nature of layered water structure [20] ionic adsorptions [21] viscosity and self-diffusion of the water layers{Formatting Citation} and dielectric properties of the interface. As one of the particular interest areas of study of the authors, diffusivity was reported to increase further away from the surface going toward bulk-like values [22] which is in accordance with the experimental measurements of Mamontov et al [23,24].…”
Section: Introductionsupporting
confidence: 87%
“…Many other theoretical studies have been systematically investigated on this surface, such as the nature of layered water structure [20] ionic adsorptions [21] viscosity and self-diffusion of the water layers{Formatting Citation} and dielectric properties of the interface. As one of the particular interest areas of study of the authors, diffusivity was reported to increase further away from the surface going toward bulk-like values [22] which is in accordance with the experimental measurements of Mamontov et al [23,24].…”
Section: Introductionsupporting
confidence: 87%
“…It is important to note that here, this MSD-sampling time was selected to be ~20–150 times the bond-exchange events’ timescales, although sufficiently long for adequate statistical sampling of such MSDs; this affords recording of rather dramatic instances of lower diffusivities at 450 and 550 K with the shoulder, or “hump”, in the 0–0.2 × 10 −9 m 2 /s region clearly discernible when motion is slowed due to involvement in reaction events. Also, the distributions in Figure 3b are clearly non-Gaussian, with a tail at higher self-diffusivities and temperatures similar to that seen in [29] for individual water molecules in hydration layers.…”
Section: Resultssupporting
confidence: 66%
“…In Figure 5, Arrhenius plots are provided for both the number of reactions per nanosecond, N , and self-diffusivity [29], D (from Figure 3), with good fit. A Student’s t -test on the resulting N - and D - activation energies of 5.12 and 4.88 kJ/mol (or 0.053 and 0.048 eV), respectively, establishes non-rejection of the null hypothesis H 0 with respective linear-regression activation-energy uncertainties of 0.43 and 0.41 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…In a highly crowded intracellular medium or within tissues, water displays particular properties, different from those of the bulk water -water diffusion is not a purely random process, being restricted due to its high viscosity and macromolecular crowding. This interfacial water is known to play a fundamental role, through the maintenance of the stable three-dimensional conformation of biomolecules and biological clusters, [1][2][3][4][5][6] and any changes in its structural or dynamical profiles are expected to have substantial consequences at the functional level. Furthermore, the dynamical behaviour of water determines the biomechanical properties of cells and the cellular architecture which are associated with cancer initiation, progression, invasiveness and metastasis.…”
Section: Introductionmentioning
confidence: 99%